Reactualization of Multicultural Instruction in Pondok Pesantren: Organism Models of PAI Development Based on Inter, Multi and Transdisciplinary - Munir, Samsul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
Contemporarily, globalization marked by every access in all fields has created a variety of problems in people's lives. In reality, the world now (as a product of globalization) is almost entirely dominated by Europe and the United States which clearly have different cultural roots with the Indonesian culture. The hegemony that occurs is not merely economical and political, but more than that, it is also the cultural project of modernity. The impact of globalization today has been able to uproot the Indonesian people from the cultural roots that become their inheritance. Dehumanization in the form of an acute moral crisis has also become a part that is almost inherent in the life of every human being. In this context, pesantren as Islamic institutions that are rich of the characteristics of the Indonesian people have strategic values in the development of a multicultural society. For the Indonesian people, the strategic role of pesantren in globalization as a moral development institution, da'wah institution, and educational institutions with a multicultural character and nationalism will greatly determine the direction and purpose of the future of the Indonesian people. The response of pesantren in addressing globalization in accordance with the roles and fields that they have worked on,